2021
DOI: 10.3390/jcm10040849
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Characteristics of Non-Intensive Care Hospitalized COVID-19 Patients: A Preliminary Report

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) is posing a threat to global health. This disease has different clinical manifestations and different outcomes. The immune response to the novel 2019 coronavirus is complex and involves both innate and adaptive immunity. In this context, cell-mediated immunity plays a vital role in effective immunity against SARS-CoV-2. Significant differences have been observed when comparing severe and non-severe patients. Since these immunological characteristics have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
1
Order By: Relevance
“…In this sense, Iwasaki and Medzhitov showed that the level of IL-6 was markedly higher in severe cases than in mild and moderate cases. Still, the levels of CD4+ T cells, CD8+ T cells, and NK cells were decreased, indicating immunosuppression in severe COVID-19 [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, Iwasaki and Medzhitov showed that the level of IL-6 was markedly higher in severe cases than in mild and moderate cases. Still, the levels of CD4+ T cells, CD8+ T cells, and NK cells were decreased, indicating immunosuppression in severe COVID-19 [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, further investigation is required to ascertain the significance of these differences. Recent research has further uncovered that residual SARS-CoV-2 can persist in various organ systems ( 17 20 ), thereby increasing oxidative stress response ( 21 ) and cytotoxic effects ( 7 ), which may contribute to LC development. The prevalence of LC is estimated to exceed 10% ( 22 , 23 ), with some reports suggesting that it could impact 50–70% ( 24 , 25 ) of hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immunity is the key factor in the complete eradication of the virus [ 4 ]; this immune pathway needs 4 to 7 days to be activated after the occurrence of the infection. If an effective adaptive antiviral response is not generated in time to suppress the virus, innate immune responses will potentiate but are unable to effectively eradicate the virus, and this also leads to systemic inflammatory responses with the irrepressible release of inflammatory cytokines [ 75 , 76 , 77 , 78 ]. Elderly patients and those with chronic diseases need a longer period of time to generate adaptive and innate immune responses because of cell senescence.…”
Section: Discussionmentioning
confidence: 99%